Stres dan hubungan beban kerja Guru Sekolah Rendah kawasan Pelajaran Tambun Tulang, Arau, Perlis - Asri, Ahmad (2010)
This study aimed to identifjl the main factors in teacher stress among teachers in primary schools in the area of education Tambun Tulang Arm, Perlis. Stress factors studied, including teachers work load factors, the constraints of time and resources, recognition and interpersonal relationships. A total of 150 teachers (N = 150) fiom six primary schools were randomly selected (cluster of clusters') to be involved in this study. A pilot study was conducted among 30 primary school teachers in a school district of Kuala Perlis in Perlis. The results showed that the level of stress among the respondents were at moderate levels. Recognition factor (alpha = 0.873) were identified as major factors of stress among the respondents. This was followed by work load factor (alpha = 0.795), factors of time and resource constraints (alpha = 0.811), and interpersonal factors (alpha = 0.860). All four of these factors have resulted in a moderate stress for primary school teachers involved. The findings from this research show that teachers experience stress at a moderate level. The findings could help the teachers identify the stress factors and workload of teachers